Comparative Learning Curves of Microscope Versus Exoscope: A Preclinical Randomized Crossover Noninferiority Study - Layard Horsfall, Hugo; Mao, Zeqian; Koh, Chan Hee; Khan, Danyal Z.; Muirhead, William; Stoyanov, Danail; Marcus, Hani J. (Frontiers in Surgery, 2022)
Background The exoscope heralds a new era of optics in surgery. However, there is limited quantitative evidence for clinical usability. Objectives To investigate the learning curve, plateau and rate of novice surgeons using the Olympus ORBEYE exoscope compared to the operating microscope (Carl Zeiss OPMI PENTERO or KINEVO 900). Methods A preclinical, randomized, crossover, non-inferiority trial assessed the performance of seventeen novice and seven expert surgeons completing the microsurgical grape dissection task “Star’s the limit”: a standardized star is drawn on a grape using a stencil with 5mm edge length. Participants cut the star and peel the star-shaped skin off the grape with microscissors and forceps, whilst minimizing damage to the grape flesh. Participants repeated the task 20 times for each device consecutively. Learning was assessed using model functions such as the Weibull function, and cognitive workload was assessed with the NASA Task Load Index (NASA-TLX). Results Seventeen novice (male:female 12:5; median years of training 0.4 [0 – 2.8 years]) and six expert (male:female 4:2; median years of training 10 [8.9 – 24 years]) surgeons were recruited. “Star’s the limit” was validated using a performance score that gave a threshold of expert performance of 70 (0-100). The modified Weibull function was the best fit for modeling the learning curves. The learning rate (ORBEYE -0.94±0.37; microscope -1.30±0.46) and learning plateau (ORBEYE 64.89±8.81; microscope 65.93±9.44) of the ORBEYE was significantly non inferior compared to the microscope group (p=0.009; p=0.027 respectively). The cognitive workload on NASA-TLX was higher for the ORBEYE. Novices preferred the freedom of movement and ergonomics the ORBEYE but preferred the visualization of the microscope. Conclusions This is the first study to quantify the ORBEYE learning curve, and the first randomized controlled trial to compare the ORBEYE learning curve to the microscope. The plateau performance and learning rate of the ORBEYE is significantly non-inferior to the microscope. This study also supports that ergonomics of the ORBEYE as reported in preliminary observational studies and highlights visualization as a focus for further future development.